Implementasi Metode Certanty Factor Untuk Diagnosa Penyakit Tanaman Tebu Hijau Pada PT. Perkebunan Nusantara VII - Darojatul Kubroh; Lena Elfianty; Jhoanne Fredricka (UNIVED Press, 2024)
This research aims to create an expert system application in diagnose green sugarcane plant diseases using the certainty factor method. Green sugar cane is one of the plantation crop commodities in Indonesia. However, cultivating green sugar cane does not escape various problems related to diseases that are likely to attack green sugar cane plants. If green sugar cane plants are attacked by disease, the yield and quality of green sugar cane will decrease which will then cause significant losses for green sugar cane farmers and green sugar plantation owners. If it is not immediately addressed, it will spread widely and worsen over time. The MySQL database can accommodate information and data from patients who consult with an expert system which can make it easy for patients to consult about green sugarcane plant diseases. The resulting expert system can make it easy for users to diagnose green sugarcane plant diseases online.